1997
DOI: 10.1074/jbc.272.52.32956
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-specific Regulation of Cl− Channels by Purinergic Receptors in Rat Submandibular Gland Acinar and Duct Cells

Abstract: Measurement of [Cl] i , BzATP in both SMG cell types largely activated the Ca 2؉ -independent, glibenclamide-sensitive Cl ؊ current, whereas UTP activated only the Ca 2؉ -dependent Cl ؊ current. We interpret this to suggest that BzATP and UTP largely activate Cl ؊ channels residing in the membrane expressing the receptor for the active nucleotide. The present studies reveal a potentially new mechanism for transcellular Cl ؊ transport in a CFTR-expressing tissue, the SMG. Coordinated action of the P 2 z (lumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
96
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 43 publications
7
96
1
Order By: Relevance
“…Previously, we showed that P2R signals evoke the membrane-specific activation of ion transporters in polarized epithelial tissues (27,28). In the present study, the stimulatory effects of luminal ATP on NKCC were partially inhibited by the blockade of luminal Cl Ϫ channels (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that P2R signals evoke the membrane-specific activation of ion transporters in polarized epithelial tissues (27,28). In the present study, the stimulatory effects of luminal ATP on NKCC were partially inhibited by the blockade of luminal Cl Ϫ channels (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports demonstrate that members of the TMEM16 (4 -7) and BEST (8,(11)(12)(13) gene families encode Ca 2ϩ -activated Cl Ϫ channels with properties much like those found in native tissues (1,(15)(16)(17)(18). TMEM16A was previously detected in a proteomics screen of exosomal proteins isolated from human parotid saliva (32) and in the apical membrane of mouse salivary acinar cells (6), whereas mouse salivary gland acinar cells express transcripts for Best2 (9).…”
Section: Ca 2ϩmentioning
confidence: 99%
“…-dependent Cl Ϫ channels are fundamental to the function of numerous organ systems such as membrane potential regulation in excitable cells (52,53) and fluid secretion by exocrine gland acinar cells (15)(16)(17)(18). Nevertheless, unequivocal molecular identification of the CaCC in these various cell types is generally lacking.…”
Section: Ca 2ϩmentioning
confidence: 99%
See 2 more Smart Citations